The Double-Edged Effect of Contracts on Alliance Performance. (September 2018) - Schilke, Oliver; Lumineau, Fabrice
Despite substantial scholarly interest in the role of contracts in alliances, few studies have analyzed the mechanisms and conditions relevant to their influence on alliance performance. In this paper, we build on the information-processing view of the firm to study contracts as framing devices. We suggest that the effects of contracts depend on the types of provisions included and differentiate between the consequences of control and coordination provisions. Specifically, control provisions will increase the level of conflict between alliance partners, whereas coordination provisions will decrease such conflict. Conflict, in turn, reduces alliance performance, suggesting a mediated relationship between alliance contracts and performance. We also contribute to a better understanding of contextual influences on the consequences of contracts and investigate the interactions of each contractual function with both internal and external uncertainties. Key informant survey data on 171 alliances largely support our conceptual model.